The poetry of R.F. Ratshi̳tanga : a critical evaluation of the poetry of protest - Milubi, Ntshavheni Alfred (My University, 1983)
Refer to the document
Thesis (M.A. (African Languages)) --University of the North, 1983
Keywords: Venda poetry; Venda language; Ratshi̳tanga, R. F. -- Criticism and interpretation; Venda poetry -- History and criticism